Bit and power loading procedures for OFDM systems with bit-interleaved coded modulation - Mutti, C.; Dahlhaus, D.; Hunziker, T.; Foresti, M. (10th International Conference on Telecommunications : ICT'2003 : February 23-March 1, 2003, Sofitel Coralia Maeva Beach Hotel, Tahiti, Papeete, French Polynesia, 2003)
We present adaptive power and bit loading schemes for a bit-interleaved coded OFDM system with perfect channel state information and square quadrature amplitude modulation constellations. In order to minimize the bit error rates at the output of the Viterbi decoder subject to bit rate and power constraints, an analytical expression for the bit error rate of a hard-decision device has to minimized with respect to the number of bits and the power assigned to the subcarrier channel. The prohibitive complexity of the optimum solution can be circumvented by a simple suboptimum two-step procedure where the bit and power loading parts are decoupled. It is shown by Monte Carlo simulations that for broadband systems with Rayleigh fading the loading procedures provides a SNR gain of up to 6 dB for an average bit error rate level of 10/sup -6/.